Carbon dioxide fluxes on a soybean field in Argentina: influence of crop growth stages - Posse Beaulieu, Gabriela (2010)
CO2 fluxes were measured in a soybean field in the Province of Buenos Aires, Argentina, with an eddy covariance system consisting of a CO2/H2O infrared gas analyzer and a sonic anemometer. The measurements were carried out between 24th December 2008 and 31st March 2009. The measurements continued to be carried out even after the growing season, in order to capture data on the CO2 fluxes of dying plants and weed plants established after it. Changes in phenology and botanical composition were accompanied with important changes in CO2 flux values and on the relative importance exercised by three meteorological variables selected to describe the environmental condition: solar radiation, air temperature and vapor pressure deficit (VPD). The maximum CO2 fluxes were recorded before noon and reached values up to approximately 1.0 mg CO2 m-2 s-1, having a relation with the global radiation and VPD values. This low value was probably associated with the few rain registered during the spring. When senescence took place, respiration processes became more important and the field acted as a source of CO2. A weak relation was found then with the environmental conditions. Carbon dioxide uptake was reestablished when the soil was covered by weeds but at a much lower rate. The maximum flux value was then around 0.3 mg m-2 s-1. Carbon dioxide flux was strongly associated with global radiation, which explained 80% of the variance.